The Economic Impact of Eko-Gastronomy in Bangli: A Multidisciplinary Analysis - Pambudi, Bondan; Arafaf , Willy; Sudjana, I Made; Ingkadijaya, Rahmat (eScience Humanity Journal, 2024)
This study examines the economic impact of eco-gastronomy in Bangli Regency, focusing on tourism revenue, job creation, and infrastructure investment through Interpretative Structural Modelling (ISM) and stakeholder interviews. Findings reveal that tourism revenue is the dominant factor driving local economic growth, influencing job opportunities and investment in infrastructure. However, challenges such as economic inequality, the dominance of large asset holders, and mismanagement of infrastructure hinder the sector’s full potential. While eco-gastronomy offers significant opportunities for enhancing local economic welfare, there is a need for improved governance, equitable benefit distribution, and sustainable management practices. Recommendations for future development emphasize fair, transparent policies, and targeted investments to ensure eco-gastronomy contributes to long-term sustainable growth and local community prosperity. Future research should adopt a multidisciplinary approach, involving marginalized communities, and focus on long-term socioeconomic and environmental impacts.